The Influence of School Principals’ Academic Supervision and Teacher Professional Development on the Quality of Learning in Elementary Schools - Purwitasari, Eti; Buchori, Achmad; Wuryandini, Endang (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aimed to examine the influence of principals' academic supervision and teachers' professional development on the quality of learning in public elementary schools. The research was conducted in public elementary schools in Wanasari District, Brebes Regency, Indonesia. A quantitative approach with an ex post facto research design was employed. The population of teachers is 211 in Wanasari District, Brebes Regency. Proportional random sampling was used to ensure representation from each school. The study involved 138 teachers selected as the research sample. Data were collected using a structured questionnaire and analyzed through descriptive statistical analysis and multiple linear regression. The results indicated that: (1) principals' academic supervision has a positive and statistically significant effect on the quality of learning; (2) teachers' professional development has a positive and statistically significant effect on the quality of learning; and (3) principals' academic supervision and teachers' professional development simultaneously have a positive and statistically significant effect on the quality of learning. These findings suggest that effective academic supervision by principals, together with continuous professional development of teachers, plays a significant role in improving the quality of learning in elementary schools. Therefore, strengthening academic supervision practices and promoting ongoing professional development are essential strategies for enhancing the quality of teaching and learning.